The Role of Technology to ESD through Science and Physics Education: A Comprehensive Bibliometric Analysis Using Biblioshiny - Mohd Zaidi Bin Amiruddin; Wahyudin Wahyudin; Andi Suhandi; Achmad Samsudin; Bayram Coştu; Kristóf Fenyvesi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study investigates the role of technology in supporting Education for Sustainable Development (ESD) through a bibliometric approach, specifically in the context of science and physics education. Through data analysis from Scopus, this study identifies research trends related to GaVaR (Gamification, Virtual Reality, and Augmented Reality) and explores the relationship between keywords, authors, and countries. The study used PRISMA in filtering the desired criteria. The findings showed a significant increase in the production of GaVaR-related articles but with significant variation in citation impact from year to year. The implication of this study is the importance of technology integration in science and physics learning to increase student engagement and understanding of sustainability issues. In addition, integrating technology in the current era indispensable, especially to assist in the learning of abstract material